Antibacterial Properties and Flavonoids Content of Some Mosses Common in Armenia: Antibacterial Properties and Flavonoids Content of Some Mosses Common in Armenia - Semerjyan, Inesa; Semerjyan, Gayane; Semerjyan, Henrikh; Trchounian, Armen (Iranian Journal of Pharmaceutical Sciences, 2020)
The present study was aimed to evaluate the antibacterial potential of ethanol, methanol, acetone, and aqueous extracts of some bryophytes common in Armenia (Mnium spinosum (Voit) Schwaegr, Brachythecium salebrosum (Web. et Mohr) B.S.G., Thuidiumrecognitum (Hedw) Lindb and Dicranum scoparium (Hedw). Antibacterial activity was determined using agar-well diffusion method against five bacterial species (Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Salmonella enterica, and S. typhimirium). The results showed that the bryophytes D. scoparium and B. salebrosum possessed high antibacterial activity in methanol extracts, whereas M. spinosum has high antibacterial activity in acetone extract. Antibacterial activity against S. aureus was comparably weaker. Ethanol extract of T. recognitum had greater antibacterial activity than the extract of M. spinosum. Of all those tested for antibacterial activity bryophytes in vitro extracts of D. scoparium have yielded the most promising results. Antibacterial activity might be caused by a high content of flavonoids in bryophytes determined. Thus, the studied bryophytes might be used to develop new antibacterial agents.